Analysis of Generator Power Requirements for Lighting Distribution Using LED Lights on a 500 DWT Sabuk Nusantara - Wati, Gusra; Suardi, Suardi; Mubarak, Azhar Aras; Fabila, Nova; Simanjuntak, Lowry Gabriel; Adila, Imam Rifqi; Myistro, Evan (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
Sabuk nusantara ship serve as the lifeline of transportation for remote, frontier, underdeveloped, and border islands (3TP), especially in areas devoid of other land and air transportation. These vessels, capable of accommodating up to 500 individuals, connect 3TP-category islands to larger ports, playing a pivotal role in sustaining the economic activities of these regions.This study focuses on the use of LED lights within ship interiors, employing the zonal cavity method. This method divides each room into three segments: the height ceiling cavity (hcc), the height room cavity (hrc), and the height floor cavity (hfc). Illumination values are then determined based on established standards for each specific room.The principal finding reveals that the lighting electricity load for the 500 DWT Pioneer Ship, utilising LED lighting, amounts to 8.74 kW. This research not only addresses technical considerations but also underscores the significance of adequate illumination for passenger comfort and the seamless operation of the ship.By concentrzating on research outcomes, this study provides valuable insights for understanding and enhancing the lighting system on Pioneer Ships. Future steps may involve implementing recommendations to improve efficiency and comfort on such vessels, ensuring the sustainability of the economic and connectivity aspects in regions reliant on these ships.